PENGARUH BIAYA REKLAME DAN PERIKLANAN PADA PT. PAPUA PASIFIK PERMAI JAYAPURA (STUDI KASUS PERIODE 2014 – 2018) - Delfia Delfia; Aftoni Sutanto (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
This study aims to determine the effect of sales promotion costs and advertising costs on operating profit in the 2014-2018 financial year. This study uses a quantitative approach. This research data uses sales promotion costs and advertising costs and is presented every month for 60 months. The research method used with the Classical Assumption Test and Multiple Regression. The results of this study indicate that: (1) sales promotion costs affect the operating profit with the value of Sig. 0.006, (2) the cost of advertising affects the operating profit with the value of Sig. 0.000 (3) counting together the costs of sales promotion and the cost of advertising have an effect on the operating profit with the value of Sig. 0,000. Test Results on R2 show that operating profit is influenced by sales promotion costs and advertising costs by 79,3% and the rest is influenced by other variables. Keywords: Promotion, advertising, operating profit costs